Does Managerial Ability Have Information Content for Capital Market Players? An Empirical Study in Indonesia - Totong, Allysa; Herusetya, Antonius (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study empirically tests the effect of managerial ability on market reaction. Managerial ability is measured using the Demerjian et al. (2012) model, while market reaction is measured using the earnings response coefficient (ERC). The study observations include samples from all public companies on the IDX listed from 2017 to 2021 with a final number of observations of 1,380 in firm-years, except for the financial sector. By using the non-probability sampling method and purposive sampling technique, and the linear multiple regression estimation model, this study found no evidence that managerial ability can be detected by the market. Our additional testing using a measure of highest level of managerial ability also found no evidence that the market can capture the information content measured by the ERC from the highest level of managerial ability. Further test also found no evidence that during the crisis period due to the COVID-19 pandemic there is no incremental information from the existence of managerial ability captured by the capital market players. The results of this study are robust considering the results of sensitivity and additional tests.